PENGARUH RESIDU PESTISIDA TERHADAP POLA POPULASI BAKTERI DAN FUNGI TANAH DI RUMAHKACA - Sulistinah, Nunik; Antonius, S; Rahmansyah, Maman (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
Pesticide Residue was Affect Bacterial and Fungal Population in the Greenhouse Soil Condition. Bacterial and fungal inhabitants were examined through agriculture soil samples. Survival of microorganism in soil was important to evaluate the mineralize process. In the greenhouse experiment, bacterial and fungal population noticed as essential assessment in soil healing with long lasting pesticide (A-soil) after the soil treated with powdered rice straw as organic matter amendment, toxic degrading bacterial as inoculants, and the both of those mixed treatments. That residue implication also assessed to B-soil (as free pesticide soil) then revised with pesticides, and also treated as followed for A-soil. Potential degradation of indigenous microorganism examined all through as setting of control (B-soil) to recognize of its original population.Those of treatments evaluated through microbial survival along 12 weeks incubation in green house environment. Bacterial and fungal populations was affect to become fluctuated along with incubation period as due to the treatments. Bacterial inhabitant was considerably higher compared to fungal population. Correlations were significantly difference with bacterial (p = 0.6654) as well as fungal (p = 0.9029) population in A-soil evaluated to B-soil habitats since the mixed treatments present to both of the soil (p0.005 = 0.6310). Organic matter alteration and certain microbe input was needed in soil contain pesticide, because at the same time the survival of microbes possibly mineralized organic matter, as well as the pesticide residue.